2016
DOI: 10.1002/lno.10379
|View full text |Cite
|
Sign up to set email alerts
|

Processes driving seasonal variability in DMS, DMSP, and DMSO concentrations and turnover in coastal Antarctic waters

Abstract: This study presents new measurements of the concentrations and turnover rates of dimethyl sulfide (DMS), dimethylsulfoniopropionate (DMSP), and dimethyl sulfoxide (DMSO) in coastal waters near Palmer Station, Antarctica, during the spring and summer of 2012–2013. Using several novel analytical and experimental techniques, we document variability in DMS, DMSP, and DMSO (DMS/P/O) concentrations and quantify dominant production and removal terms in the mixed layer DMS budget. Our results demonstrate considerable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 76 publications
5
38
0
Order By: Relevance
“…The latest Southern Ocean climatology indicates that the WAP is not a particular hotspot of DMS production (Jarníková and Tortell 2016), although this may reflect a shortage of published datasets, particularly from the marginal ice zone. Two time series from the Palmer LTER show highest DMS concentrations in January between 5 and 15 nM (Asher et al 2017;Herrmann et al 2012), which compare well with the climatological mean for January of 10.8 ± 6.9 (SD) nM for the whole Austral Polar province (Lana et al 2011). A recent continuous 5-year time series at Rothera shows large seasonal fluctuations in northern Marguerite Bay, with considerably higher concentrations in January, reaching an average of 24 ± 35 (SD) nM and a maximum of 160 nM in January 2015 (Webb et al in review).…”
Section: Organic Sulphur Compoundsmentioning
confidence: 99%
“…The latest Southern Ocean climatology indicates that the WAP is not a particular hotspot of DMS production (Jarníková and Tortell 2016), although this may reflect a shortage of published datasets, particularly from the marginal ice zone. Two time series from the Palmer LTER show highest DMS concentrations in January between 5 and 15 nM (Asher et al 2017;Herrmann et al 2012), which compare well with the climatological mean for January of 10.8 ± 6.9 (SD) nM for the whole Austral Polar province (Lana et al 2011). A recent continuous 5-year time series at Rothera shows large seasonal fluctuations in northern Marguerite Bay, with considerably higher concentrations in January, reaching an average of 24 ± 35 (SD) nM and a maximum of 160 nM in January 2015 (Webb et al in review).…”
Section: Organic Sulphur Compoundsmentioning
confidence: 99%
“…Zooplankton play diverse roles in the cycling of many elements in the ocean including iron, zinc, sulfur, and mercury (Fowler, 1977;Asher et al, 2016;Baines et al, 2016;Schmidt et al, 2016;Gorokhova et al, 2018). However, their greatest importance to global biogeochemistry is likely derived from their roles in the biological carbon pump (BCP; Buitenhuis et al, 2006;Turner, 2015;Steinberg and Landry, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In summer, the average concentration order was AAd > DMSPt > DMS > DMSPd along the three transects; this result was consistent with the order in the surface seawater (Table 1). Higher values of DMS than DMSPd might be produced through the intracellular cleavage of phytoplankton DMSPp catalyzed by the enzyme DMSP lyase and the photochemical and biological reduction of dimethylsulfoxide (DMSO) to DMS (Asher et al, 2017). In contrast, the higher values of AAd than DMSPt indicated that there were terrestrial sources of AAd aside from the contribution of in situ DMSP degradation along the three transects.…”
Section: Biogeochemical Processes Influencing Aad Dms and Dmsp In Tmentioning
confidence: 98%